Consumers’ Preference of Ready to Drink Coffee Food Pairing: Check-All-That-Apply (CATA) Approach - Zulfa Nur Hanifa; Dase Hunaefi; Budi Nurtama (Jurnal Penelitian Tanaman Industri, 2021)
Coffee products expand at the same rate as consumer needs. Ready-to-drink (RTD) coffee is a ready-to-drink coffee beverage that is convenient to consume. RTD coffee pairs well with a variety of foods, this combination will produce a sensory trait called Food Pairing. The purpose of this study was to determine the sensory attribute characteristics of RTD coffee and its nourishments using CATA method, as well as the sensory attribute intensity change using modified RATA method. The research process was carried out by initial screening of the panelists, followed by Focus Group Discussion (FGD) to determine sensory attribute and sensory testing, which was carried out using the Home Used Test (HUT). Responses were processed using statistical software XLSTAT and generated a food pairing sensory profile of RTD coffee. The results showed that consumers like RTD coffee paired with chocolate wafer. The "Coffee-Chocolate Wafer" profile features a creamy and thick texture along with a sweet and chocolate flavor, making it near-ideal food set based on CATA result. The "Coffee- Coconut Biscuit" set's profile has a crunchy texture and a bitter from the coffee and coconut flavors. The "Coffee-Potato Chips" profile features a crisp texture, salty, umami, roasted beef flavor, and oily mouthfeel. When paired, the intensity of each attribute increases, decreases, or even persists. RTD coffee product innovation can be made by combining the attributes of coffee and chocolate wafers as the ideal and preferred pairing, resulting in RTD coffee variants with sweet, creamy, chocolate, and crunchy attributes.Keywords : RTD coffee, food pairing, CATA  AbstrakPreferensi Konsumen pada Food Pairing Kopi Ready To Drink dengan Pendekatan Check-All-That-Apply (CATA)Produk olahan kopi berkembang pesat karena menyesuaikan dengan kebutuhan konsumen. Kopi ready to drink (RTD) adalah produk minuman kopi yang siap saji dan siap dikonsumsi sehingga dinilai lebih praktis. Kopi RTD sering dikonsumsi dengan berbagai makanan pendamping, perpaduan ini akan menghasilkan sifat sensori jika dikonsumsi secara bersamaan, yang disebut dengan Food Pairing. Penelitian ini bertujuan untuk mengetahui karakteristik atribut sensori dari perpaduan kopi RTD dengan makanan pendampingnya dengan metode CATA, serta perubahan intensitas atribut sensori dengan modifikasi metode RATA. Penelitian ini dilakukan dengan screening awal panelis, Focus Group Discussion (FGD) untuk menentukan atribut sensori, dan pengujian sensori yang dilakukan secara Home Used Test (HUT). Respon yang didapatkan diolah menggunakan software XLSTAT dan menghasilkan profil sensori food pairing kopi RTD. Hasil pengujian menunjukkan konsumen menyukai kopi RTD yang dipasangkan dengan wafer cokelat. Profil pasangan “Kopi-Wafer Cokelat” memiliki tekstur creamy, thick, rasa sweet, dan cokelat sehingga mendekati pasangan ideal berdasarkan hasil CATA. Profil pasangan “Kopi-Biskuit Kelapa” memiliki tekstur crunchy, rasa pahit dari kopi, coffee flavor, dan coconut flavor. Profil pasangan “Kopi-Keripik kentang” memiliki tekstur crispyness, rasa salty, umami, roasted beef, dan mouthfeel oily. Intensitas setiap atribut akan mengalami perubahan yaitu meningkat, tetap, atau menurun saat dipasangkan. Inovasi produk kopi RTD dapat dilakukan dengan menggabungkan atribut wafer kopi dan cokelat sebagai pasangan ideal dan disukai, sehingga menghasilkan varian kopi RTD dengan atribut sweet, creamy, chocolate, dan crunchy.Kata kunci : kopi RTD, food pairing, CATA